Analyses of adsorption behavior of CO2, CH4, and N2 on different types of BETA Zeolites - Henrique, Adriano (2019)
The adsorption equilibrium and kinetics of CO2, CH4, and N2 on three types of BETA zeolites were investigated at different temperatures and a defined partial pressure range from dynamic breakthrough experiments. The adsorbed amount followed the decreasing order of CO2 >CH4 >N2 for all studied materials. For the same ratio of SiO2/Al2O3, the Na-BETA-25 zeolite showed a higher uptake capacity than H-BETA-25, due to the presence of a Na+ cationic center. Comparing the same H+ compensation cation, zeolite H-BETA-25 expressed a slightly higher adsorption capacity than H-BETA-150. Regarding the selectivity of gases, based on their affinity constants, H-BETA-150 displayed the best ability. The adsorption kinetics was considered using the zero-length-column (ZLC) technique. Response surface methodology (RSM) was applied to evaluate the interactions between adsorption parameters and to describe the process.